The wolf : culture, nature, heritage - Convery, Ian, 1965-; Davis, Peter, 1947 November 15-; Lloyd, Karen (Writer of The gathering tide); Nevin, Owen; Van Maanen, Erwin (Heritage matters series, 2023)
New insights into the changing human attitudes towards wild nature through the depiction of wolves in human culture and heritage.